Faktor-faktor yang Mempengaruhi Profitabilitas Bank Umum Syariah di Indonesia Periode 2016-2020 - Natalia Sumule; Wirman (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2022)
Knowing the factors that affect profitability, which is represented by ROA at Islamic Commercial Banks (BUS) in Indonesia, is the goal of this research. The independent variables used include the ratio of NPF, FDR, and BOPO while the dependent variable used is ROA. Multiple linear regression analysis method is the analytical method used in this study. The results of hypothesis testing show that NPF and FDR have no significant effect on ROA, in contrast to BOPO which shows a significant negative effect on ROA. However, simultaneously NPF, FDR, and BOPO have a significant effect on ROA. The final conclusion in this study, the factor that affects the profitability of BUS is only one variable, namely BOPO. This means that the higher the BOPO value, the decrease in profitability will be more pronounced so that banks are advised to control banking operational costs and on the other hand be able to increase banking operating income